PENGARUH KONSEP KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA SISWA SMK SE-KABUPATEN TOBA SAMOSIR - Rosinta Romauli Situmeang; Nurmaidah Ginting (Asian Journal of Innovation and Entrepreneurship, 2016)
The challenges faced by today's young generation a lot in the field of employment, the entrepreneurial education leads to survival and self-reliance should be ditonjolkan.Pendidikan entrepreneurship is the curriculum that is being activated for the students. This study will focus on the concept of entrepreneurial interest in entrepreneurship among students SMK Toba Samosir. The aim of this study was to examine and analyze the influence of entrepreneurial concepts simultaneously and partially on interest in entrepreneurship. Research hypothesis is the concept of entrepreneurship significant effect on students' interest in entrepreneurship SMK-Toba SamosirThis research is descriptive quantitative nature of explanatory research, and the research that is based on partial test results showed that the variables Creativity positive and significant effect on the interests of Entrepreneurship Student SMK Toba Samosir, based on partial test results indicating that the variable Innovative positive effect and significant impact on student interest in entrepreneurship SMK Toba district Samosir.Hasil simultaneous testing showed that Creativity and Innovative positive and significant effect on the interests of Entrepreneurship. The value of creativity and innovative variables that may explain the interest in entrepreneurship in vocational students Toba Samosir Se of 72.8% while the remaining 27.2% is explained by the independent variables were not examined and Innovative Variable towards interest in entrepreneurship is more dominant than the variable of creativity against the interest in entrepreneurship.